Spatio-temporal patterns in floral resources and plant-pollinator network structure in the Alaskan Arctic - Khorsand, Roxaneh S.; Ginn, Zachary R.; Sancier-Barbosa, Flavia (Frontiers in Plant Science, 2025)
Predicting shifts in plant-pollinator communities as a result of warming requires an accurate understanding of floral availability, insect activity, and spatio-temporal patterns of plant-insect interaction. Plant-insect visitor network studies from the High Arctic have demonstrated high generalization and rapid temporal turnover, yet comparable data are lacking for the Low Arctic. We worked in two tundra plant community types on the North Slope of Alaska in 2022 and 2023 to construct the first plant-insect visitor networks for this region of the Arctic and document temporal patterns of floral resource availability and insect visitation. We found temporal differences in floral availability between community types. Both floral density and the number of species in anthesis peaked earlier in the dry heath tundra compared to the moist acidic tundra. In addition, Hymenopteran visitation rates showed a bimodal peak (early- and late-season) while Dipteran visitation rates showed a unimodal pattern. Network complexity peaked earlier in the dry compared to the moist community. Our results suggest that temporal heterogeneity in floral resources between plant community types may increase the duration of floral availability for insects at a landscape scale. Given this region’s low species diversity and increasing vulnerability to extreme weather events, spatio-temporal heterogeneity in floral resources may play a critical role in the resiliency of this system.